Cryopreservation of Cord Blood Nucleated Cells Using Non-Penetrating Cryoprotectant PEO-1500 - Babijchuk, Lyubov A.; Mykhailova, Olga A.; Ryazantsev, Vladimir V.; Zubov, Pavel M.; Migunova, Regina K. (Problems of Cryobiology and Cryomedicine, 2016)
Development of wash-free cryopreservation methods for cord blood nucleated cell fraction, including the population of hematopoietic stem/progenitor cells, is an actual task for their long-term storage. Present investigation involved the technique of cord blood nucleated cells cryopreservation, comprising the isolation of cell population by the original two-step centrifugation method, the treatment with non-penetrating cryoprotectant polyethylene oxide with molecular weight of 1500 (PEO-1500) and freezing by the two-step program. This technique enabled to preserve more than 72% CD45+ and 75% CD34+ cells with the viability indices of correspondingly 83 and 91% and higher. Herewith, an increased content of reactive oxygen species (42.7 Â± 6.3%) on the background of high cell number and their viability may be considered as a cellsâ€™ physiological response to the effect of cryopreservation factors. Probl Cryobiol Cryomed 2016; 26(1):24-34.